Analysis of Code-Mixing and Code-Switching in The Puella Id Youtube Podcast - Rizky Alifia Annisa; Meiga Ratih Tirtanawati; Chyntia Heru Woro Prastiwi; Siti Yulaikah, Rizky Alifia Annisa (PT. Pustaka Cendekia Publisher, 2024)
This study examines code-mixing and code-switching in PUELLA ID YouTube podcast videos. The main goals of this research are to describe the types of code-mixing and code-switching found in the PUELLA ID podcast, compare the English and Indonesian code-mixing and code-switching used by the guest stars, and identify the factors that cause code-mixing and code-switching in the podcast. The writer utilizes descriptive and qualitative research methods. The data sources consist of two selected podcast videos on YouTube PUELLA ID. In the first podcast video, two types of code mixing, insertion and alternation, are used. Only one kind of code-switching, intra-sentential, is present. The second podcast video also utilizes insertion and alternation code mixing, along with different types of code-switching: Tag, Inter-sentential, and Intra-Sentential. Insertion code-mixing and Intra-sentential code-switching dominate the types of code mixing and code-switching used in both podcast videos.